Molecular Detection of Multidrug Resistant Staphylococcus aureus from Retail Meat Samples of Tirupati Town, Andhra Pradesh - Khan Pathan, Naswar; Putturu, Ramya; Chinta Siva, Swetha; Vinayaka, Siddartha P; Yasarla, Suresh; Dharmana , Sharmila (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Staphylococcus aureus causes variety of diseases in both animals and humans. Foods of animal origin may be an important source for  the transfer of antimicrobial-resistant S. aureus and antimicrobial resistance genes to humans. Hence the present study was designed  to detect multidrug resistant S. aureus among retail meat samples of Tirupati town, Andhra Pradesh (India). A total of 250 samples in  the form of meat/swabs (chicken 100, mutton 60, beef 30, pork 30, sea meat 30) were collected from different retail outlets of Tirupati  town, and processed for isolation and identification of S. aureus by cultural method and molecular characterisation by PCR. S. aureus was confirmed targeting nuc gene and all the isolates were subjected to antibiotic sensitivity test by disc diffusion method against 10  antibiotics. Results showed that out of 250 meat samples, 200 were positive for S. aureus with an overall prevalence of 80.0% (200/250)  by cultural method and 68.0% (136/200) of them were confirmed by PCR. Antimicrobial sensitivity test revealed higher resistance to  cefoxitin (85.29%) and ceftriaxone (66.91%) compared to other selected antibiotics. They showed high sensitivity to co-trimoxazole  (66.91%) but exhibited lower sensitivity to vancomycin (8.82%). This study revealed a high prevalence of S. aureus from chicken and sea  meat samples by cultural and PCR methods, respectively, which indicates that contamination of S. aureus was common in retail meat  shops. By enhancing hygienic practices and quality control measures at meat processing facilities the contamination with food borne  pathogens can be reduced.
Keywords: Antibiotic sensitivity; Food poisoning; Meat samples; , nuc gene; S. aureus.